Odpowiedzi

Najlepsza Odpowiedź!
2010-02-17T15:38:35+01:00
28*17-28*15=28*(17-15)=28*2=56
134*135-133*135=(134-133)*135=1*135=135
31*15-62*7=31*(15-2*7)=31*(15-14)=31*1=31
12*13-6*26=13*(12-6*2)=13*(12-12)=13*0=0
13*49-26*27=13*(49-2*27)=13*(49-54)=13*(-5)=(-65)
57^2-57*55=57*(57-55)=57*2=114
12 4 12
2010-02-17T15:39:47+01:00
28*(17-15)=28*2=56
135*(134-133)=135*1=135
31*(15-2*7)=31*1=31
13*(12-6*2)=13*0=0
13*(49-27*2)=13*(49-54)=13*(-5)=-65
57*(57-55)=57*2=114
5 3 5
2010-02-17T15:43:54+01:00
28*17-28*15=28(17-15)=28*2=56
134*135-133*135=135(134-133)=135*1=135
31*15-62*7=31(15-2*7)=31*1=31
12*13-6*26=13(12-6*2)=13*0=0
13*49-26*27=13(49-2*27)=13*(-5)=(-65)
57(do kwadratu)-57*55 =57-57*57*55=57(57-55)=57*2=114
3 1 3